Ph.D. Supervision - Saveriades, Alexis (My University, 2026)
Member of Advisory Committee Subject area: DARK TOURISM Candidate: Mrs. Chryso Panayidou TO DATE: Taught requirements: Completed., Comprehensive Exam: Completed., Proposal: Completed CURRENTLY (February 2021): In research phase